Risk Factors of Oral Cancer in India: A Systematic Review and Meta-analysis - Mocherla, Monica; Krishnappa, Pushpanjali; John, Denny (Indian Journal of Medical and Paediatric Oncology, 2025)
Oral cancer is associated with several well-known risk factors, including the use of betel quid, alcohol consumption, and tobacco smoking. Studies regarding oral cancer risk factors vary based on the different subgroups identified in the Indian context.This systematic review, meta-analysis, and meta-regression aggregate data from various studies on oral cavity cancer risk factors in India.From September 20 to 30, 2024, we searched for English studies on PubMed, ScienceDirect, and Google Scholar. Two independent reviewers selected studies based on title/abstract and full text, with adjudication by a third author. We utilized the JBI checklist for critical appraisal of case–control studies. The data provided information on participant demographics, cases and controls, evaluated risk factors, and odds ratios. A random effects model produced pooled estimates for each risk factor.Fifteen case–control studies conducted in the Indian population were included in the analysis. Our meta-analysis concludes that any form of tobacco use is the primary risk factor for oral cavity cancer, with risk rising consistently alongside the duration of use. Additionally, daily alcohol consumption significantly increases this risk. Chronic trauma to the oral mucosa also plays a substantial role in the development of oral cavity cancer. Sensitivity analysis and meta-regression indicated that factors such as sample sizes, case–control ratio, and study region had no significant impact. Funnel plots assessing publication bias in studies reporting tobacco smoking and chewing revealed no significant asymmetry, and Egger's test was nonsignificant (p > 0.05).There is sufficient evidence for the role of tobacco in both smoking and smokeless forms as a risk factor for oral cavity cancer in India.
Keywords: risk factors; oral cancer; systematic review; meta-regression; India